Does the concentration of the treadmill of production predict US EPA environmental violations across states?: a test of green criminological propositions from ecological disorganization theory - Lynch, Michael J. (Critical criminology, 2023)
Green criminologists have employed treadmill of production (ToP) literature to develop explanations for green/environmental crimes, and to describe ToP effects on the enforcement of environmental regulations. That view, however, has not been widely applied empirically. The present study assesses a green political economic explanation of environmental offending across US states, and examines whether the distribution of one measure of the ToP (the concentration of manufacturing facilities), is related to five measures of environmental violations and noncompliance across US states for 2015 US EPA ECHO data. Controlling for the alternative criminological argument that enforcement deters environmental offenders and reduces environmental violations, the outcomes suggest a ToP/manufacturing concentration effect for three of the five measures of environmental violations and noncompliance. The implications and limitations of these findings and further research are discussed.